GAMBARAN PENGETAHUAN PETUGAS TB-HIV DALAM PENEMUAN DAN AKSES PENGOBATAN (Studi di Layanan Komprehensif Berkesinambungan di Puskesmas Kota Semarang) - Puspita Kristina Kusumawati; Lintang Dian Saraswati; Martini Martini; Retno Hestiningsih (Jurnal Kesehatan Masyarakat (Undip), 2021)
HIV and Tuberculosis are two public health problems of global concern. People living with HIV (PLWH), can develop opportunistic infections because they do not know their HIV status. With the vulnerability of PLWH to opportunistic infections, especially TB, it is necessary to routine HIV tests on positive and suspected TB patients. The performance of TB-HIV health officers is one that determines the detection of tuberculosis and HIV cases. The purpose of this study was to describe the knowledge related to the performance of officers in finding and accessing TB-HIV treatment at the Primary Public Health Center in Semarang City. This study used a descriptive research design with cross sectional methods, with 19 research subjects. Data reliability using data auditing by checking the flow of data analysis. The results showed that the officers had good knowledge conducted good screening for TB-HIV suspects. But some officers do not get enough training HIV. The advice for the health department is to make more training for the officers.